Standardized relative humidity index can be used to identify agricultural drought for summer maize in the Huang-Huai-Hai Plain, China. (November 2021) - Wu, Xia; Wang, Peijuan; Ma, Yuping; Gong, Yanduo; Wu, Dingrong; Yang, Jianying; Huo, Zhiguo
Highlights: Standardized Relative Humidity Index (SRHI) was derived based on relative humidity. SRHI identified agricultural drought was more accurately than SPI in the HHH Plain. SRHI can reflect actual damage to summer maize caused by drought in the HHH Plain. SRHI can be used to monitor and assess drought for summer maize at a regional scale. Abstract: Maize ( Zea mays L.) is a staple food in most parts of the world, and is also one of the most important food crops in China. Frequent occurrences of drought events can lead to summer maize drought disasters. The air relative humidity has the predominant superiority in spatio-temporal continuity compared to precipitation. In this study, meteorological data, phenophase observations, and disaster records of summer maize in the Huang-Huai-Hai Plain (the HHH Plain) were jointly used to establish a Standardized Relative Humidity Index (SRHI) to identify and characterize summer maize drought disasters and to provide support for summer maize drought monitoring, prevention, and mitigation. Results showed that the threshold values of SRHI10 (at ten-day scale) during the V0-VT (planting-tasseling) and VT-R6 (tasseling-physiological maturity) periods were −0.05 and −0.25, and the values of SRHI30 (at monthly scale) during the V0-VT and VT-R6 periods were −0.10 and −0.50, respectively. Both SRHI10 and SRHI30 could reasonably identify the actual drought conditions of summer maize in the HHH Plain. Validation with independent drought samples showed that SRHI10 was the most effective among SRHI10, SRHI30, and SPI10 . The province-wide validation within 55 years also revealed that the drought of summer maize identified with SRHI10 was basically consistent with historical disaster records, with the average identification accuracy being of 94.0%. Additionally, SRHI10 could indicate the occurrence of drought relatively earlier than actual drought records during both the V0-VT and VT-R6 periods of summer maize. Therefore, the spatio-temporal distribution characteristics of drought for summer maize in the HHH Plain were mapped based on SRHI10 . Drought occurred in 38% and 25% of the years during the V0-VT and VT-R6 periods, respectively, from 1961 to 2015. The drought extent during the V0-VT period was greater than during the VT-R6 period in 64% of the study years, indicating that summer maize in the HHH Plain was more exposed to drought during the vegetative growth period. The spatial distribution pattern of drought severity increased from the south to north during the V0-VT period, while during the VT-R6 period it exhibited the same spatial pattern to drought frequency. The drought in both the V0-VT and VT-R6 periods of summer maize showed the increasing trend in most of the HHH Plain of China. SRHI10 can be a useful indicator for monitoring and assessing summer maize drought disasters at regional scale. This index can also provide a new method for agricultural drought analysis.